Steroidobacter gossypii sp. nov., isolated from cotton field soil. Issue 8 (3rd August 2021) - Huang, Rui-Rui; Ge, Xian-Feng; Chen, Xin-Kai; Yang, Shen-Rong; Zhen, Cheng; Wen, Zhi-Qiang; Li, Ya-Nan; Liu, Wen-Zheng
Abstract : A Gram-negative bacterium, designated S1-65 T, was isolated from soil samples collected from a cotton field located in the Xinjiang region of PR China. Results of 16S rRNA gene sequence analysis revealed that strain S1-65 T was affiliated to the genus Steroidobacter with its closest phylogenetic relatives being ' Steroidobacter cummioxidans ' 35Y (98.4 %), ' Steroidobacter agaridevorans ' SA29-B (98.3 %) and Steroidobacter agariperforans KA5-B T (98.3 %). 16S rRNA-directed phylogenetic analysis showed that strain S1-65 T formed a unique phylogenetic subclade next to ' S. agaridevorans ' SA29-B and S. agariperforans KA5-B T, suggesting that strain S1-65 T should be identified as a member of the genus Steroidobacter . Further, substantial differences between the genotypic properties of strain S1-65 T and the members of the genus Steroidobacter, including average nucleotide identity and digital DNA–DNA hybridization, resolved the taxonomic position of strain S1-65 T and suggested its positioning as representing a novel species of the genus Steroidobacter . The DNA G+C content of strain S1-65 T was 62.5 mol%, based on its draft genome sequence. The predominant respiratory quinone was ubiquinone-8. The main fatty acids were identified as summed feature 3 (C16:1 ω6 c /C16:1 ω7 c ), C16 : 0 and iso-C15 : 0 . In addition, its polar lipid profile was composed of aminophospholipid, diphosphatidylglycerol, phosphatidylethanolamine and phosphatidylglycerol. Here, we propose a novel species of the genus Steroidobacter : Steroidobacter gossypii sp. nov. with the type strain S1-65 T (=JCM 34287 T =CGMCC 1.18736 T ).